DEGRADASI KANDUNGAN FORMALIN PADA DAGING AYAM BROILER (Gallus domesticus) BERFORMALIN DENGAN PERENDAMAN LARUTAN LIDAH BUAYA (Aloe vera) - N.L. Nurfi; Tatang Sopandi (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2014)
An experimental research has been carried out to investigate the effect of aloe vera (Aloe vera) concentration on reduce of formaldehyde levels, and tenderness of broiler meat. This study have used 20 chest of broiler meat weighing 100 g respectively. Meat have been soaked in 10% formalin solution for 1 h and randomly divided into 5 groups of treatments. Each groups have soaked in aloe vera 0%, 15%, 30%, 45% and 60% solution for 1 h. Formaldehyde level in meat have analized by spectrophotometer at λ 415 nm. Tenderness of meat have observared by phenetrometer. The results showed meat soaking in aloe vera 15%, 30%, 45% and 60% solution significant effect (P<0.05) to reduce formaldehyde level and meat tenderness. The results of this study it can concluded the administration of a solution of aloe vera (Aloe vera) 60% can reduce formaldehyde levels high of 92.13% and a yield of broiler meat tenderness formalin maximum of 490.25 mm/ 100g /10 seconds. Keywords: Aloe vera, broiler chicken meat, degradation of formaldehyde, tenderness of meat